The trouble with secrets - Milliner, Naomi (Quill Tree Books, an imprint of HarperCollinsPublishers, 2025)
"Twelve-year-old Becky has great expectations placed upon her. Not only does she need to be as perfect as her older brother and sister, but her upcoming bat mitzvah needs to be perfect, too. She is the rabbi's daughter, after all. The trouble is, Becky's intentions often lead her astray. At least when she plays the flute, she feels like the best version of herself--until playing the flute causes Becky to do something not so perfect: keep a secret from her parents. Then Becky discovers that Sara, her 'perfect' sister, has an even bigger secret, one that could turn the family upside down. The sisters couldn't be more ready to keep each other's secret safe--until the excitement turns to guilt, and Becky is forced to make an impossible choice"--